2024
DOI: 10.3390/brainsci14030194
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Exercise on Brain-Derived Neurotrophic Factor (BDNF) Levels and Clinical Outcomes in People with Parkinson’s Disease: A Systematic Review and Meta-Analysis

Daan G. M. Kaagman,
Erwin E. H. van Wegen,
Natalie Cignetti
et al.

Abstract: Introduction: Exercise therapy may increase brain-derived neurotrophic factor (BDNF) levels and improve clinical outcomes in people living with Parkinson’s disease (PD). This systematic review was performed to investigate the effect of exercise therapy on BDNF levels and clinical outcomes in human PD and to discuss mechanisms proposed by authors. Method: A search on the literature was performed on PubMed up to December 2023 using the following key words: Parkinson’s disease AND exercise, exercise therapy, neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Despite the intense research efforts in pharmacological, rehabilitative, and surgical fields, PD remains a chronic neurodegenerative disease, lacking a disease-modifying therapy. Systematic review and meta-analysis supported the efficacy of physical activity and exercise, reflecting a growing interest in the promotion of rehabilitation programs as a disease-modifying treatment for PD ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Despite the intense research efforts in pharmacological, rehabilitative, and surgical fields, PD remains a chronic neurodegenerative disease, lacking a disease-modifying therapy. Systematic review and meta-analysis supported the efficacy of physical activity and exercise, reflecting a growing interest in the promotion of rehabilitation programs as a disease-modifying treatment for PD ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, several authors suggested that the neuroprotective effects of exercise in PD animal models were mediated by neurotrophic, anti-inflammatory, and angiogenic factors ( 7 , 9 , 14 , 20–23 ). Indirect evidence supports the neuroprotective role of exercise also in people with PD, potentially involving changes in neurotrophic and anti-inflammatory factors ( 18 , 19 , 24 ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Brain-derived neurotrophic factor (BDNF) is a key protein involved in neuroplasticity events after exercise ( Kaagman et al, 2024 ). BDNF is a widely studied neurotrophic factor that plays an important regulatory role in neuronal function and brain health ( Jaberi and Fahnestock, 2023 ).…”
Section: Molecular Mechanisms Of Exercise-induced Neuroplasticitymentioning
confidence: 99%